Alto (‘high’/‘tall’), bajo (‘low’/‘short’), profundo (‘deep’) and superficial (‘superficial’): From Dimensional to Qualitative Meaning. Lexicographic Proposal - Ynduráin Pardo de Santayana, Carlos (2024)
The adjectives alto, bajo, profundo and superficial present a network of meanings of metaphorical origin in which these words are related to qualitative concepts apparently far from the physical world. These concepts can be grouped, in the case of high and low, within the categories MOOD (ánimo bajo), MORAL (bajos pensamientos) and IMPORTANCE (alto ejecutivo). In the case of deep and shallow, their qualitative link is maintained with that which, in a general way, we can identify with the ESSENCE OF THINGS (sentimientos profundos). These two pairs of antonyms present important parallels in their metaphorical evolution processes. This article analyzes the cognitive basis of these semantic extensions and discusses their classification for lexicographic treatment.